PENGGUNAAN SISTEM BARCODE DALAM RANGKA PENGAMANAN AKTA NOTARIS - Imananda Noegroho, Rr. Dwini (Program Pascasarjana Universitas Sunan Giri Surabaya, 2019)
According to the law notarial deed has specific or special technique, language, form and section. Notarial deed is also one of the written evidence as stated in the Civil Code Article 1866. Indonesia Notary Community utilizes barcode technology advancements to checking the authenticity of a deed namely by storing and reading information digitally about deed made by the Notary Public regarding the deed?s title and deed?s number. This research shows that the use of a barcode system with the aim of securing a notarial deed must be mandated and used for good purposes namely for interested parties and this is a form of Notary services to the public so that the notarial deed is kept safe and cannot be misused by those who want to abuse